Compulsory compassion : a critique of restorative justice - Acorn, Annalise E. (Law and society series (Vancouver, B.C.), 2004)
"In Compulsory Compassion, Annalise Acorn, a one-time advocate for restorative justice, deconstructs the rhetoric of the restorative movement. Drawing from diverse legal, literary, philosophical, and autobiographical sources, she questions the fundamental assumptions behind that rhetoric: that we can trust wrongdoers' performances of contrition; that healing lies in a respectful, face-to-face encounter between victim and offender; and that the restorative idea of right-relation holds the key to a reconciliation of justice and accountability on the one hand, with love and compassion on the other."--Jacket